2000
DOI: 10.1287/inte.30.3.202.11653
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Sustainability in Service Operations at Scandic Hotels

Abstract: The case of Scandic Hotels shows, first, that sustainable strategies and practices can be just as useful in service operations as in manufacturing operations; and second, that such strategies and practices can support a corporate turnaround effort. Scandic Hotels, Nordic Europe's biggest hotel chain, was on the verge of collapse in the early 1990s. A new CEO, Roland Nilsson, turned the company around by introducing two business principles, decentralized management and sustainable development. The company's new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(109 citation statements)
references
References 0 publications
1
104
0
4
Order By: Relevance
“…This study illuminates different aspects: first, there are already studies on the adoption of EPs in the hotel sector [16][17][18][19][20][21], and some of them have already indicated the competitive advantages of implementing proactive initiatives for certain environmental issues: [22] finds that performance levels increase as environmental proactivity grows; [23] finds that the link between environmental management practices and financial performance is stronger for proactive hotels; [24] suggest that a proactive environmental stance is vital to maintain the image of hotels; and [20] claim that hotels proactive on environmental issues have a higher level of economic performance. However, to the best of our knowledge, there are no studies specifically focused on studying the differences in the results obtained depending on whether the EPs are adopted voluntarily or under pressure, and few studies are focused on small hotels.…”
Section: Introductionmentioning
confidence: 88%
“…This study illuminates different aspects: first, there are already studies on the adoption of EPs in the hotel sector [16][17][18][19][20][21], and some of them have already indicated the competitive advantages of implementing proactive initiatives for certain environmental issues: [22] finds that performance levels increase as environmental proactivity grows; [23] finds that the link between environmental management practices and financial performance is stronger for proactive hotels; [24] suggest that a proactive environmental stance is vital to maintain the image of hotels; and [20] claim that hotels proactive on environmental issues have a higher level of economic performance. However, to the best of our knowledge, there are no studies specifically focused on studying the differences in the results obtained depending on whether the EPs are adopted voluntarily or under pressure, and few studies are focused on small hotels.…”
Section: Introductionmentioning
confidence: 88%
“…Collaboration with suppliers and customers is essential for driving environmentally sustainable practices (Carter and Carter, 1998;Zhu and Sarkis, 2004); incentives are needed to reduce suppliers' risks when adopting these collaborative processes (Goodman, 2000); so focal companies need to educate their suppliers and have their suppliers educate each other (Rao and Halt, 2005). In a SSCM context, Van Hoof and…”
Section: Sscm Governance Mechanismsmentioning
confidence: 99%
“…Previous research on sustainability in the tourism sector originated two decades ago as an analysis of the adoption of environmentally friendly practices among other works [9,[14][15][16][17][18][19][20] and its economic impact [21]. Sustainability impacts the economy in three ways: (1) it has a direct effect through energy savings; (2) it has an indirect effect because an environmentally friendly image creates a competitive advantage; and (3) the business gains the advantage of being positioned as a green company [14][15][16][17][18][19][22][23][24][25][26][27][28]. To a lesser extent, previous research has found that there is a social impact [2,11] and an impact on the acquisition of unique capabilities [2,29,30].…”
Section: Evolution Of Eco-innovationmentioning
confidence: 99%